Use of a membrane flow cell to measure average mass transfer coefficients in denitrifying biofilms - García López, L. A. (2002)
Average mass transfer coefficients within denitrifying biofilms were determined during biofilm growth with an inert compound (LiCl) in a membrane flow cell at different flow conditions, until the biofilm reached (pseudo-) steady state. Similar values were obtained for the steady-state mass transfer coefficients of LiCl within the different biofilms. However, those coefficients were higher during the transient period of biofilm growth for the biofilm developed under the highest upflow velocity.